NLRP3 inflammasome: A likely target for the treatment of allergic diseases. Issue 9 (3rd July 2018) - Xiao, Yichen; Xu, Wenna; Su, Wenru
Summary: Allergic diseases, such as asthma, rhinitis, dermatitis, conjunctivitis, and anaphylaxis, have recently become a global public health concern. According to previous studies, the NLRP3 inflammasome is a multi‐protein complex known to be associated with many inflammatory conditions. In response to allergens or allergen/damage‐associated molecular signals, NLRP3 changes its conformation to allow the assembly of the NLRP3 inflammasome complex and activates caspase‐1, which is an evolutionarily conserved enzyme that proteolytically cleaves other proteins, such as the precursors of the inflammatory cytokines IL‐1β and IL‐18. Subsequently, active caspase‐1 cleaves pro‐IL‐1 and pro‐IL‐18. Recently, accumulating human and mouse experimental evidence has demonstrated that the NLRP3 inflammasome, IL‐1β, and IL‐18 are critically involved in the development of allergic diseases. Furthermore, the application of specific NLRP3 inflammasome inhibitors has been demonstrated in animal models. Therefore, these inhibitors may represent potential therapeutic methods for the management of clinical allergic disorders. This review summarizes findings related to the NLRP3 inflammasome and its related factors and concludes that specific NLRP3 inflammasome inhibitors may be potential therapeutic agents for allergic diseases.